Concrete mix design using crushed pebble as replacement material in concrete mixture - Goh, H.C (Universiti Malaysia Sarawak, UNIMAS, 2009)
The result of an experimental study on mechanical properties of concrete with different type of coarse aggregate and water/cement ratios is presented. In this study concrete with 28 days target compressive strength of 30 N/mm2 with workability at least 30mm were produce using pebble as aggregate and compare with the concrete using microtonalite as aggregate. The aims of the study were to investigate and determine the effect of pebble and microtonalite on mechanical properties of concrete and to determine the strength that can be achieved by both of the aggregates. The experimental focus on concrete mixes with a water binder ratio of 0.4, 0.45 and 0.50 without using admixture and superplasticizer. The mechanical properties of concrete were measured by conducted the cube compressive strength test. 28 days test result has indicated that the concrete mixture prepared with microtonalite produced the higher compressive strength, compare with concrete mixture prepared with pebble. However, concrete mixture prepared with pebble was able to reach the target compressive strength of 30 N/mm2 by using water binder ratio of 0.45 and the result is 35.71 N/mm2 with workability of 50mm.